Overview and recent challenges [in Africa agriculture trade monitor 2023] - Odjo, Sunday P.; Traoré, Fousseini; Zaki, Chahir (AKADEMIYA2063, 2023)
This is the sixth Africa Agriculture Trade Monitor (AATM), an annual flagship publication of the International Food Policy Research Institute (IFPRI) and AKADEMIYA2063. The AATM provides an overview of trade in agriculture in Africa, including analysis of short- and long-term trends and drivers behind Africa’s global trade, intra-African trade, and trade within Africa’s regional economic communities. The AATM is supported by the United States Agency for International Development (USAID) and the German Federal Ministry for Economic Cooperation and Development (BMZ). The six chapters of this 2023 AATM report are as follows.